SPECT/CT IN DETECTION OF BONE METASTASES IN BREAST AND PROSTATE CANCERS - E. A. Glushkov; A. G. Kislichko (Сибирский онкологический журнал, 2016)
Most cancers have the ability to metastasize to the bones. Absolute leaders among them are breast and prostate cancers. Progressive growth of bone metastases causes serious metabolic disturbances in the body and loss of skeletal integrity thus resulting in the development of serious complications leading to death. The need for early detection of secondary bone cancer as well as poor images obtained by using available imaging methods contributed to the creation of multimodality SPECT/CT systems. The article discusses the use of SPECT/CT in detection of metastatic involvement of the skeleton. It describes the basic principles of SPECT/CT clinical applications. In addition, both the advantages and disadvantages of the hybrid technology are shown. The results of different studies assessing the diagnostic efficacy of SPECT/CT in the detection of secondary bone tumors are compared.